Advances in physiological computing - Gilleade, Kiel; Fairclough, Stephen H. (Human-Computer Interaction Series,, 2014)
In the domain of physiological computing, human physiology is directly monitored and used as input to a technological system. Signals from the brain and body can be used to infer a user's intentions and psychological state which enables a physiological computing system to respond and adapt in an appropriate fashion.  A computer game could modify its level of difficulty according to the player's motivation or a word processor could disable incoming e-mail notifications when the user is concentrating. Physiological computing is an exciting area of research which provides a speculative vision of how we may interact with technology in the future. The field is inherently interdisciplinary and encapsulates a significant breadth of knowledge from neuroscience to engineering. Advances in Physiological Computing provides a broad overview across this emerging area of research and emphasizes the common ground between the different disciplines in the field.